Hydrogeochemical Assessment of Groundwater in Neyveli Basin, Cuddalore District, South India - Prasanna, Mohan Viswanathan; Chidambaram, S.; Senthil Kumar, G.; Ramanathan, A.L.; Nainwal, H.C. (Springer Verlag, 2010)
In the light of progressive depletion of groundwater reservoir and water quality deterioration of the Neyveli basin, an investigation on dissolved major constituents in 25 groundwater samples was performed. The main objective was detection of processes for the geochemical assessment throughout the area. Neyveli aquifer is intensively inhabited during the last decenniums, leading to expansion of the residential and agricultural area. Besides semi-aridity, rapid social and economic development stimulates greater demand for water, which is gradually fulfilled by groundwater extraction. Groundwaters of the study area are characterized by the dominance of Na + K over Ca + Mg.HCO3 was found to be the dominant anion followed by Cl and SO4. High positive correlation was obtained among the following ions: Ca–Mg, Cl–Ca,Mg, Na–K, HCO3–H4SiO4, and F–K. The hydrochemical types in the area can be divided into two major groups: the first group includes mixed Ca–Mg–Cl and Ca–Cl types. The second group comprises mixed Ca–Na–HCO3 and Ca–HCO3 types. Most of the groundwater samples are within the permissible limit of WHO standard. Interpretation of data suggests that weathering, ion exchange reactions, and evaporation to some extent are the dominant factors that determine the major ionic composition in the study area.